Dual role of transient receptor potential ankyrin 1 in respiratory and gastrointestinal physiology: From molecular mechanisms to therapeutic targets - Tekulapally, Kavya Reddy; Lee, Ji Yeon; Kim, Dong Seop; Rahman, Md. Mahbubur; Park, Chul-Kyu; Kim, Yong Ho (Frontiers in Physiology, 2024)
The transient receptor potential ankyrin 1 (TRPA1) channel plays a pivotal role in the respiratory and gastrointestinal tracts. Within the respiratory system, TRPA1 exhibits diverse distribution patterns across key cell types, including epithelial cells, sensory nerves, and immune cells. Its activation serves as a frontline sensor for inhaled irritants, triggering immediate protective responses, and influencing airway integrity. Furthermore, TRPA1 has been implicated in airway tissue injury, inflammation, and the transition of fibroblasts, thereby posing challenges in conditions, such as severe asthma and fibrosis. In sensory nerves, TRPA1 contributes to nociception, the cough reflex, and bronchoconstriction, highlighting its role in both immediate defense mechanisms and long-term respiratory reflex arcs. In immune cells, TRPA1 may modulate the release of pro-inflammatory mediators, shaping the overall inflammatory landscape. In the gastrointestinal tract, the dynamic expression of TRPA1 in enteric neurons, epithelial cells, and immune cells underscores its multifaceted involvement. It plays a crucial role in gut motility, visceral pain perception, and mucosal defense mechanisms. Dysregulation of TRPA1 in both tracts is associated with various disorders such as asthma, Chronic Obstructive Pulmonary Disease, Irritable Bowel Syndrome, and Inflammatory Bowel Disease. This review emphasizes the potential of TRPA1 as a therapeutic target and discusses the efficacy of TRPA1 antagonists in preclinical studies and their promise for addressing respiratory and gastrointestinal conditions. Understanding the intricate interactions and cross-talk of TRPA1 across different cell types provides insight into its versatile role in maintaining homeostasis in vital physiological systems, offering a foundation for targeted therapeutic interventions.